Development of an Android-Based Physics Interactive E-Module Equipped with Problems with Scaffolding in Applying the Concept of Light Waves - Alvia Quthrotun Nada; Taqwa, Muhammad Reyza; Supriana, Edi; Suwasono, Purbo (Yayasan Nurul Yakin Bunga Tanjung, 2022)
The purpose of this study was to develop and determine the validity and practicality of learning media in the form of an Android-based E-Module equipped with questions with scaffolding on light wave material. In this study, the Research and Development (R&D) model with the 4-D method was used. The stages of 4D development include define, design, develop, and disseminate, but in this study only up to the design stage with validity and practicality tests. Product validation was carried out by three media and material expert validators, namely 1 lecturer and 2 high school physics teachers, while the practicality test was carried out by 48 students of class XI MIPA SMAN 1 Paciran. The research results obtained quantitative and qualitative data. Analysis of quantitative data using percentages and categorized criteria of validity and practicality. The results of this research and development are in the form of an Android-based physics interactive E-Module product with light wave material. From the validation test by the validator, the average percentage of results for media and material validation is 90% with very valid criteria. This shows that the material presented is in accordance with the curriculum so that it can support student learning. In the validation test results of practice questions with scaffolding, the average percentage is 97% and the percentage of evaluation questions is 96% with very valid criteria. This shows that the practice questions and evaluation questions that have been made valid are used by students in studying light waves and are validly included in the developed e-module. From the results of the practicality test, an average percentage of 85% was obtained in the very practical category. This shows that the product developed is very valid and very practical so it is worth investigating its effectiveness so that it can further support physics learning in understanding the concept of light waves, both used independently and in school learning.